Susceptibility and Resistance Mechanisms During Photodynamic Therapy of Melanoma - Li, Xin-Ying; Tan, Liu-Chang; Dong, Li-Wen; Zhang, Wan-Qi; Shen, Xiao-Xiao; Lu, Xiao; Zheng, Hong; Lu, Yuan-Gang (Frontiers in Oncology, 2020)
Melanoma is the most aggressive malignant skin tumor and arises from melanocytes. The resistance of melanoma cells to various treatments results in rapid tumor growth and high mortality. As a local therapeutic modality, photodynamic therapy has been successfully applied for clinical treatment of skin diseases. Photodynamic therapy is a relatively new treatment method for various types of malignant tumors in humans and, compared to conventional treatment methods, has fewer side effects, and is more accurate and non-invasive. Although several in vivo and in vitro studies have shown encouraging results regarding the potential benefits of photodynamic therapy as an adjuvant treatment for melanoma, its clinical application remains limited owing to its relative inefficiency. This review article discusses the use of photodynamic therapy in melanoma treatment as well as the latest progress made in deciphering the mechanism of tolerance. Lastly, potential targets are identified that may improve photodynamic therapy against melanoma cells.